Enforcement of the Environmental Protection by the means of Economic Activity Regulations: International Law Perspective (Part 1) (Summary) - E. F. Pushkareva (Московский журнал международного права, 2013)
The articles addresses three directions in the International law, those developments may lead to the efficiency increase of in enforcement of the environmental protection by the means of Economic Activity Regulations. Those directions include the Environmental Protection in the WTO, Environmental Provisions of International Investment Agreements and Environmental Policy of the International Financial Institutions.